Petrogenesis and metallogenic significance of late Mesozoic granites in the Akjilga mining area, Tajikistan: constraints from geochronology and geochemistry - Li, Dong-Ren; Hu, Gui-Ang; Qin, Xiao-Feng; Zhao, Yu-Lei; Mo, Hui; He, Wen-Lu (Frontiers in Earth Science, 2023)
The Akjilga (Акджилга) mining area in Tajikistan sits in the central part of the Pamir syntaxis in the western part of the Indo-Eurasia collisional orogenic belt. Recently, the mineralization phenomena of skarn-type tin polymetallic ore bodies and dolomite-type rare-earth metals in the copper polymetallic mining area have been reported. However, the limited knowledge on the genesis of granite and its relationship with mineralization in this area hinders further research. Here, the Late Mesozoic granite rocks in the mining area were studied by petrology, geochemistry, and zircon U-Pb dating. The results showed that the rocks comprise majorly porphyric biotite syenogranite and minorly porphyric biotite monzogranite. The zircon U-Pb age of the porphyric biotite syenogranite was 108.3 ± 2.0 Ma, highlighting the Early Cretaceous period. The porphyric biotite syenogranite features high silicon and potassium contents and low iron, magnesium, calcium, sodium, titanium, and phosphorus contents. Furthermore, their aluminum saturation indexes were 1.11-1.21. Therefore, they were classified as high-potassium calc-alkaline strong peraluminous rocks. Trace-element analysis showed the enrichment of large ionic lithophile elements and light rare-earth elements (REEs); the deficiency of high-field-strength elements and heavy REEs; and the negative anomalies of Nb, P, and Ti. Compared with ordinary granites, the porphyric biotite syenogranite exhibits a higher differentiation index (91.20-93.96) and strong negative Eu anomaly (0.05-0.26), as well as a low Zr content and abnormally low Nb/Ta, Zr/Hf, Y/Ho, ∑LREE/∑HREE ratios. Therefore, the rocks are considered highly differentiated I-type granites with good Sn polymetallic and rare-metal prospecting potentials, and it resulted in the subduction-collision of the Rushan-Pshart ocean between the Middle Pamir block and the South Pamir block during the northward subduction process of the Late Mesozoic New Tethys ocean (Shyok ocean).